Sam makes trouble - Warner, Gertrude Chandler, 1890-1979.; Life, Kay (Morton Grove, Ill. : A. Whitman, 2002)
When Benny's friend comes to visit the Alden house with his two-year-old brother Sam, the younger boy makes trouble everywhere he goes.
"A Boxcar Children early reader"--Cover.
1.9
K-3
Keywords: Boxcar children (Fictitious characters) -- Juvenile fiction; Orphans -- Juvenile fiction; Human behavior -- Juvenile fiction; Boxcar children (Fictitious characters) -- Fiction; Orphans -- Fiction; Behavior -- Fiction; Boxcar children (Fictional characters) -- Fiction; Orphans -- Fiction; Human behavior -- Fiction